The Greek Non-Paradigm of Economic and Business Development, and Comparisons with South Korea - Elias Sanidas (SPOUDAI - Journal of Economics and Business, 2014)
A series of wrong policies since the 1980s transformed the Greek economy into a problematic one and almost ready to collapse; for example, artificial increases in employment in nonproductive public services entailing low productivity; increasing wages above those guaranteed by productivity increases; an increasing budget deficit which was used primarily for consumption; and joining the Euro zone too early. Some of the consequences were the relative de-industrialization of the country; a huge public debt and the consequential international indebtedness; and the impossibility to recover quickly after the recent global financial crisis. Some stylized modeling facts about all these issues facilitate our understanding of both the Greek and Korean economies. Furthermore, the parallel examination of the Korean economy during the same period, whenever necessary and possible, contrasts this country's correct choice of economic policies with those of Greece: thus, what Korea did, Greece did not and vice versa.
Keywords: O11; O23; O24; O; 43; O52; H50; H62; 330; productivity; wages; Euro area; stagflation; exports; politics and economics; Greece; South Korea